Synergizing management, technology and innovation in generating sustainable and competitive business growth : proceedings of the International Conference on Sustainable Collaboration in Business, Information and Innovation (SCBTII 2020), Bandung, Indonesia, July 10, 2020 - International Conference on Sustainable Collaboration in Business, Information and Innovation (2020 : Bandung, Indonesia); Hendayani, Ratih; Rachmawati, Indira; Ayuningtias, Hani Gita; Cahyaningsih; Dennyra, Dania Syanetta (London : Routledge, 2021)
Sustainable Collaboration in Business, Technology, Information and Innovation (SCBTII 2020) Proceeding's topic deals with ``Synergizing Management, Technology and Innovation in Generating Sustainable and Competitive Business Growth``. This proceeding offers valuable knowledge on how research can be applied to support the government by introducing a policy of economic transformation in solving various challenges and driving the business sector to gain the ability to create sustainable competitive advantages, which will lead to sustainable, competitive and quality growth. The subjects in this Proceeding are classified into four tracks: Strategy, Entrepreneurship, Economics; Digital-Based Management; Finance and Corporate Governance; and Accounting. These valuable researches inside this proceeding can help academicians, professionals, entrepreneurs, researchers, learners, and other related groups from around the world who have special interest in theories andpractices in the field of digital economy for global competitiveness.
OCLC-licensed vendor bibliographic record.
Keywords: Sustainable development -- Congresses; Information technology -- Economic aspects -- Congresses; Technological innovations -- Economic aspects -- Congresses; BUSINESS & ECONOMICS / Economics / General